2018
DOI: 10.1002/jcla.22386
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of interleukin 18 gene polymorphisms in alopecia areata

Abstract: The rs1946518 (-607C>A) and rs187238 (-137G>C) polymorphisms were found associated with alopecia areata disease. The study suggests that IL-18 rs187238 and rs1946518 SNPs may be the cause of the AA susceptibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“… 47 Despite our negative findings regarding rs187238, rs1946518, and rs549908 SNPs of IL18 gene, the latter two variants were a significant difference in Korean AA cases in comparison to the healthy controls, 47 while the former two variants were associated with AA in the Turkish population. 3 Therefore, IL18 variants are considered major contributors to the etiopathogenesis of AA in some populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 47 Despite our negative findings regarding rs187238, rs1946518, and rs549908 SNPs of IL18 gene, the latter two variants were a significant difference in Korean AA cases in comparison to the healthy controls, 47 while the former two variants were associated with AA in the Turkish population. 3 Therefore, IL18 variants are considered major contributors to the etiopathogenesis of AA in some populations.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 It presents with different sizes and patterns of nonscarring hair loss mediated by targeted, organ-specific inflammatory responses of the hair follicles. 3 , 4 There are several subtypes of alopecia, with patchy AA forming 90% of the cases. The remaining 10% include alopecia totalis (AT), alopecia ophiasis (AO), and alopecia universalis (AU), the last one being the severest and the most differentiated form of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…AA is a highly prevalent, chronic, and relapsing autoimmune disease that targets hair follicles. IL18 is a significant pro-inflammatory cytokine that is present in high levels in AA patients (Celik and Ates, 2018). Recent data have suggested the possible role of IL17 in AA pathogenesis (Ramot et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The genotype distribution of IL-18-rs187238 C > G was statistically meaningfully different in patients with alopecia areata and controls (p = 0.0014). The GG genotype and G allele prevalence were also higher in these sufferers (p = 0.0003 and p = 0.0010, respectively) [43]. In other relevant studies, Migita et al (2008) assessed the relationship between IL-18-rs187238 C > G and -rs1946518 T > G with liver disease progression in patients with chronic HBV.…”
Section: Experimental Standpointmentioning
confidence: 93%
“…Moreover, Celik et al (2018) revealed that the genotype distribution of IL-18-rs1946518 T > G statistically signi cantly differed among alopecia areata sufferers and controls (p = 0.0008). The GG + GT genotype distribution and G allele frequency in this SNP were higher in the case group (p = 0.001 for both) [43]. Although current results differ from the abovementioned studies, they are consistent with those evaluating the association between this SNP and liver-related aberrations.…”
Section: Experimental Standpointmentioning
confidence: 95%